2017
DOI: 10.1108/ict-03-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between onboarding experience and turnover intention: intervening role of locus of control and self-efficacy

Abstract: Purpose The purpose of this paper is to find industry wise differences in relationship between onboarding experience (OE) and turnover intention (TI). An attempt has been made to find the intervening role of psychological variables such as locus of control and self-efficacy. Design/methodology/approach An online questionnaire was administered to 596 newcomers in five industrial sectors: fast-moving consumer goods, information technology (IT), pharmaceuticals, automobile manufacturing, and hospitality. The qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(82 citation statements)
references
References 78 publications
0
18
0
3
Order By: Relevance
“…Evidence has shown that having an internal locus of control is a strong predictor of better psychological adjustment to cancer: behavioral scientists have long been interested in understanding how an individual’s locus of control relates to coping and adjustment ( Knappe and Pinquart, 2009 ; Galvin et al, 2018 ). Recent research highlights that internal locus of control generates positive emotions and lessens negative ones ( Crisson and Keefe, 1988 ; Gupta et al, 2018 ). Thus, internal locus of control lowers the perceived level of distress ( Ryan and Deci, 2008 ), threat, and depression ( Arraras et al, 2002 ; Goldzweig et al, 2016 ) while improving the quality of life ( Sharif and Khanekharab, 2017 ; Toscano et al, 2020 ) among patients.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that having an internal locus of control is a strong predictor of better psychological adjustment to cancer: behavioral scientists have long been interested in understanding how an individual’s locus of control relates to coping and adjustment ( Knappe and Pinquart, 2009 ; Galvin et al, 2018 ). Recent research highlights that internal locus of control generates positive emotions and lessens negative ones ( Crisson and Keefe, 1988 ; Gupta et al, 2018 ). Thus, internal locus of control lowers the perceived level of distress ( Ryan and Deci, 2008 ), threat, and depression ( Arraras et al, 2002 ; Goldzweig et al, 2016 ) while improving the quality of life ( Sharif and Khanekharab, 2017 ; Toscano et al, 2020 ) among patients.…”
Section: Introductionmentioning
confidence: 99%
“…The contractual worker also demonstrates organizational cultural behaviors like employees and interacts socially as a member of the workgroup (Bujacz et al, 2017). When contractual workers have more distance away from normal workplace socialization, the psychological contract connection is not as fused (Bujacz et al., 2017; Gupta et al., 2018). Our study fills gaps in research explaining contractual worker psychological fusion within employer–worker interactions.…”
mentioning
confidence: 99%
“…Self-efficacy has a significant effect on decisions (intentions) to become entrepreneurs (Chen et al, 1998;McGee et al, 2009;Wilson et al, 2007) Some recent findings also showed that it was not much different from previous (Bellò et al, 2018;Gupta et al, 2018;Schmutzler et al, 2018;Tiwari et al, 2017;Zhang and Cain, 2017). ESE is an important factor that will directly affect EI (Krueger et al, 2000).…”
Section: Hypothesis Developmentmentioning
confidence: 83%